ADVANCES IN HUMAN RESOURCE MANAGEMENT IN THAILAND THROUGH THE DIMENSIONS OF WELL-BEING AT WORK: A SYSTEMATIC LITERATURE REVIEW - Srisook, Masaya; Pasunon, Prasopchai (Academic Journal Phranakhon Rajabhat University, 2025)
Human resource management in Thailand is an important gear that allows organizations to effectively drive through many dimensions to ensure that employees in the organization achieve good holistic well-being, according to this research article aims to collect and synthesize related literature to show the progress of human resource management in Thailand through the lens of workplace health from 2020 to 2024. A systematic literature review was conducted by collecting research articles related to Human Resource Management and Well-being, published between 2020 and 2024, from the Scopus database and the Thai Journal Citation Index Center (TCI). The framework for searching (PICO Framework) set criteria for selecting works (Inclusion Criteria) and excluding works (Exclusion Criteria). The selected works were collected using a Data Extraction Sheet and then analyzed and synthesized for use in order. The research results found that Human Resource Management plays an important role in developing policies and measures that promote employee happiness and well-being, as well as in developing important skills. This leads to highly efficient work systems for organizational development and sustained enhancement of human resource management capabilities. Promoting employee well-being is a crucial factor that positively influences organizational performance. In the context of Thailand, various organizations strive to advance human resource management to promote progress through the dimension of workplace well-being, which includes (1) promoting physical and mental health, (2) achieving work-life balance, (3) fostering skill and knowledge development and (4) building an organizational culture that fosters well-being. However, the above dimensions are another important approach that helps drive and develop organizations or agencies to progress and lead to the enhancement of human resource management effectively and effectively for organizations or agencies on the basis of sustainable well-being